HEMATITE-GAMMA ALUMINA BASED SOLID CATALYST DEVELOPMENT FOR BIODIESEL PRODUCTION FROM PALM OIL - Bryan
Indonesia is the biggest crude palm oil (CPO) producer in the world, with projected national production reaching 52,3 million tons in 2021. In order to achieve 23% renewable energy mix in 2025, the government has established the B30 policy, where diesel is mixed with fatty acid methyl ester (FAME) that is obtained from transesterification reaction of CPO. Catalyst that is commonly used is homogeneous catalyst, but free fatty acid content within the feed needs to be minimized because of its susceptibility to soap formation that could reduce biodiesel yield. Therefore, heterogeneous catalysts are developed due to its capability in avoiding soap formation and recyclability for sustainable use. However, several heterogeneous catalysts utilization needs more methanol, longer reaction time and higher reaction temperature so that other catalyst options need to be studied for optimal biodiesel production. The aim of this research is to investigate the performance of Fe2O3/?-Al2O3 catalyst in biodiesel production from palm oil and the influence of certain factors to catalyst performance. From the carried out transesterification process, biodiesel in the range of 73,6 – 87,6% FAME content was obtained according to the determined experimental design. It can be concluded that the catalyst composition, the methanol-oil ratio, and the catalyst loading have a significant effect on the FAME content of the biodiesel. Hematite has strong affinity for fatty acids, so a larger hematite surface area will result in a higher fatty acid absorption capacity. The addition of excess methanol can shift the equilibrium towards the product and reduce the contact inhibition between the reactants and the active site of the catalyst, thereby increasing the conversion of the reaction. On the other hand, a higher amount of catalyst loading can result in an increase in FAME content when accompanied by an increase in the hematite content of the catalyst. It can be concluded that the best variation from this experiment was the hematite content of 16%, the catalyst loading of 6%, and the methanol-oil ratio of 12:1 which resulted in the FAME content of 87,6%.